Proceedings of the 5th International Conference on Multimodal Interfaces 2003
DOI: 10.1145/958432.958480
|View full text |Cite
|
Sign up to set email alerts
|

Modeling multimodal integration patterns and performance in seniors

Abstract: Multimodal interfaces are designed with a focus on flexibility, although very few currently are capable of adapting to major sources of user, task, or environmental variation. The development of adaptive multimodal processing techniques will require empirical guidance from quantitative modeling on key aspects of individual differences, especially as users engage in different types of tasks in different usage contexts. In the present study, data were collected from fifteen 66-to 86-year-old healthy seniors as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Many researchers have called for systems that offer multiple modalities and are able to switch between them to suit the user, environment or message being delivered [2,6,7,9,12]. Research has shown that adaptable technology such as this can deliver notifications in a manner that is more acceptable Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have called for systems that offer multiple modalities and are able to switch between them to suit the user, environment or message being delivered [2,6,7,9,12]. Research has shown that adaptable technology such as this can deliver notifications in a manner that is more acceptable Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…However, that work did not examine the differences between target and distractor notifications with older persons. As research suggests that older users have different expectations and requirements from technology than younger users [7,12], there is a need to further investigate multimodal reminder design for this group. This paper presents an experiment to investigate the disruptiveness and performance of different notification modalities when delivering target and distractor notifications to older users.…”
Section: Introductionmentioning
confidence: 99%
“… Intermodal lag in the sequential presentation of information [90] may cause significant delay issues for complex tasks, especially under numerous, rapid repetitions of a motor task.  Using different granularities of feedback for different categories can have undesired effects on the relative amount of motor learning in each domain.…”
Section: Disadvantagesmentioning
confidence: 99%
“…without temporal overlap, denoted as "SEQ"). Further analysis shows that most of the subjects have adopted predominantly (with over 70% consistency) either simultaneous (87%, 20/23) or sequential (8.7%, 2/23) temporal patterns between speech and pen gestures [39], [40].…”
Section: Temporal Relationshipsmentioning
confidence: 99%